DIAGNOSTIC VALUE AND PROGNOSIS OF BACTERIAL MENINGITIS SCORE TEST TO DETERMINE BACTERIAL MENINGITIS AT RSUD DR SOETOMO SURABAYA - Anindita Diva Zeriana; Paulus Sugianto; Betty Agustina Tambunan; Agnes Dwi Maharani Callista (Journal of World Future Medicine, Health and Nursing, 2026)
Meningitis is a life-threatening neurological infection requiring rapid diagnosis and management. Clinical symptoms often overlap between bacterial, viral, and tuberculous causes, making early differentiation challenging. The Bacterial Meningitis Score (BMS) was developed to support early risk stratification. This study evaluates the diagnostic value and prognostic relevance of BMS in suspected meningitis cases at RSUD Dr. Soetomo Surabaya. A retrospective cross-sectional study was conducted using medical records of patients suspected of meningitis at RSUD Dr. Soetomo from 2023–2025. BMS components and clinical data were analyzed, including cerebrospinal fluid findings, peripheral blood results, and clinical manifestations. Diagnostic accuracy and prognostic outcomes were assessed using descriptive and comparative analysis. Among 43 patients, bacterial meningitis accounted for 25%, while tuberculous meningitis (37.5%), other neurological disorders (31.25%), and viral meningitis (6.25%) were more prevalent. Most patients were classified as low risk based on BMS. The score demonstrated better performance in ruling out bacterial meningitis than confirming it, supported by a high negative predictive value. However, diagnostic accuracy was limited by overlapping clinical features and incomplete cerebrospinal fluid data. Prognosis was more strongly associated with Glasgow Coma Scale (GCS), where lower scores correlated with poorer outcomes and increased mortality risk. BMS is useful for early risk stratification and exclusion of bacterial meningitis but must be combined with clinical and laboratory evaluation to improve diagnostic accuracy and patient outcomes.